Peningkatan Hasil Belajar Siswa Kelas IV Melalui Model Pembelajaran Problem Based Learning Pada Materi Yesus Mewaratakan Kerajaan Allah Di SD Negeri 9 Cinta Maju - Resinda Silalahi (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
Improving the Learning Outcomes of KLS IV Students through a Problem-Based Learning Model on the Material Jesus Proclaims the Kingdom of God in SD Negeri 9 Cinta Maju. This research was motivated by the low learning achievement of grade IV students of SD N 9 Cinta Maju in catholic religious subjects, especially on the material Jesus proclaiming the kingdom of God through His parables and miracles. This is because Catholic religious learning tends to be teacher-centered by relying more on the lecture method. Therefore, this research was conducted with the aim of improving student learning outcomes in catholic religious education, especially on the material Jesus proclaims the kingdom of God through parables and His Miracles through the Problem Based Learning Model in grade IV SD Negeri 9 Cinta Maju year Lesson 2023/2024. This research belongs to the type of class action research (PTK) conducted with 2 Cycles. The subjects in this study were grade IV students of SD Negeri 9 Cinta Maju.The techniques and data collection tools used were tests, conservation / observation and documentation while the data analysis used was the analysis of student learning outcomes from two aspects, namely affective aspects and cognitive learning outcomes of students. The results showed an increase in student creativity in learning catholicism using the Problem Based Learning (PBL) method. With the problem-based learning method, students have the skills to think critically and analytically so that student learning outcomes can increase above the average score and students can more easily understand and understand the subject matter about the proclamation of the kingdom of God and also His miracles.So that students have the ability to relate the material to the reality faced and encountered daily.